ANALYSIS OF THE EFFECT OF LEADERSHIP STYLES, MOTIVATION, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT FINANCIAL EDUCATION AND TRAINING AGENCY - Abdul Muis, Muhammad; Kamal, Fahmi; Frandika, Dodi (Dinasti International Journal of Digital Business Management, 2021)
This study aims to analyze the effect of leadership styles, motivation, and work discipline on employee performance at Financial Education And Training Agency The research methodology used is a quantitative method with cross-section data and primary data obtained from questionnaires. Mechanical sampling uses the purposive sampling method with the data in 2019. The data analysis technique used is multiple linear regression to test the validity, reliability test, the test model stability, linearity test, normality test, classic assumption test (test multicollinearity, heteroscedasticity test) and hypothesis testing t-statistic and f-statistic to examine the effect together with a significance level of 5%. The results of this study show that partial variables of motivation, work discipline, and leadership styles have a positive and significant on employee performance. Meanwhile, independent variables of motivation, work discipline, and leadership styles simultaneously together have a significant relationship to the dependent variables of employee performance. The coefficient of determination from this study showed 64.46% result. I show that the variation of the independent variables of motivation, work discipline, and leadership styles can explain the rise and fall of the dependent variable variation employees performance is 64.46% while the remaining of 35.54% is affected by other independent variables.